Changes in health behaviours and body mass index after a breast cancer diagnosis: results from a prospective cohort study. Issue 4 (July 2019) - Barbosa, Ana; Costa, Ana Rute; Fontes, Filipa; Dias, Teresa; Pereira, Susana; Lunet, Nuno
Abstract : The aim of the study was to describe changes in health behaviours and BMI after breast cancer diagnosis, depicting the potential influence of sociodemographic, clinical and psychological characteristics. A total of 428 breast cancer patients were prospectively followed for 3 years, since diagnosis. At the end of follow-up, women were classified regarding their adherence to recommendations for cancer prevention, prediagnosis and after 3 years, including not smoking, alcohol consumption up to one drink per day, intake of at least five portions per day of fruits and/or vegetables, physical activity and body mass index (BMI) less than 25.0 kg/m 2 . To quantify associations between patients' characteristics and changes in adherence to each recommendation, age, education and cancer stage-adjusted odds ratio (OR) with 95% confidence intervals (CIs) were calculated. Among women adhering to each recommendation before diagnosis, 54.1% reduced their physical activity, 32.4% became overweight or obese and 6.1% reduced fruits and/or vegetables intake, but there were virtually no changes in alcohol consumption or smoking. Older and more educated participants were more likely to reduce their physical activity (OR=4.71, 95% CI: 1.17–18.99; OR=11.53, 95% CI: 2.20–60.53, respectively). Among participants not following each recommendation before diagnosis, 29.1% stopped smoking, 24.6% reduced alcohol consumption, 9.9% became physically active, 7.8% increased fruits and/or vegetables intake and 3.3% reduced their BMI to less than 25.0 kg/m 2 . Older women were less likely to become physically active (OR=0.32, 95% CI: 0.14–0.75). Breast cancer patients showed some positive changes in their health behaviours after diagnosis. However, there is a large margin for improvement, which highlights the importance of health promotion interventions in this context.